2006
DOI: 10.5433/1679-0359.2006v27n2p289
|View full text |Cite
|
Sign up to set email alerts
|

Falhas da reprodução na pecuária bovina de corte com ênfase para causas infecciosas

Abstract: ResumoNa pecuária bovina de corte especializada na cria de bezerros a eficiência da reprodução é um dos aspectos de maior destaque para o sucesso financeiro do investimento. Na presente revisão serão abordados os principais parâmetros utilizados para avaliar o desempenho reprodutivo de vacas de corte criadas extensivamente, bem como as principais causas infecciosas de falhas na reprodução que comprometem os custos da produção. Palavras-chave: Bovinos, reprodução, IBR, BVD, leptospirose AbstractThe reproductive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0
17

Year Published

2014
2014
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(29 citation statements)
references
References 8 publications
0
12
0
17
Order By: Relevance
“…There are different causes for these reproductive problems and leading serious economic losses for the production chain (Junqueira and Alfieri 2006). Infectious diseases such as bovine genital campylobacteriosis (BGC) and bovine trichomonosis (BT) constitute two of the main causes of reproductive disorders in dairy herds (Alves et al 2011).…”
Section: Introductionmentioning
confidence: 99%
“…There are different causes for these reproductive problems and leading serious economic losses for the production chain (Junqueira and Alfieri 2006). Infectious diseases such as bovine genital campylobacteriosis (BGC) and bovine trichomonosis (BT) constitute two of the main causes of reproductive disorders in dairy herds (Alves et al 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Reproductive disorders of infectious origin in cattle are considered to be multietiological because different microorganisms such as bacteria, viruses, fungi and protozoa may be responsible for the impaired reproductive performance of affected herds. Serological techniques have provided a substantial of information regarding the epidemiological profiles of cattle herds relative to certain etiologies (JUNQUEIRA; ALFIERI, 2006). In this study, the animals were found to be negative for brucellosis, IBR and BVD indicating no circulation of these pathogens in the herd.…”
Section: Resultsmentioning
confidence: 58%
“…As with abortion, repeated breeding also has other infectious causes such as campylobacteriosis, trichomoniasis, and genital mycoplasmosis, as well as non-infectious causes such as trauma, genetic and hormonal disorders, and ovarian cysts (JUNQUEIRA; ALFIERI, 2006).…”
Section: Discussionmentioning
confidence: 99%